El control del otro. Sacrificios en la sociedad heroica griega - Montes Miralles, Mª Yolanda (’Ilu. Revista de Ciencias de las Religiones, 2009)
The following pages deal with the function of sacrifices in the iliadic epic. On the one hand, we will look into those contexts where sacrifices are merely mentioned and will judge their purposes and the role that they play within alterity relationships between heroes and deities. On the other, we will examine the four only examples of a detailed description of the ritual in the poem, which will also enable us to consider how fixed their verbal and non-verbal language is. This sacrificial system, invoking reciprocity repeatedly, is included in the language of heroic φιλ της (τιμ , anger, action, pity…) whether a specific sacrifice is addressed to gods or not. The pattern is not identical in all the cases but all of them seem to be prime examples of fear/control of the other, who may be mortal… or immortal.